DESIGNING STORYTELLING INSTRUCTION FOR SENIOR HIGH SCHOOL SPEAKING - Biuti Badarul Alam Nimas Puspita Arruum; Wardah Wardah; Yuniarti Yuniarti (FKIP UM Pontianak, 2022)
This research aimed at designing and developing the procedure of storytelling technique activities in teaching speaking narrative text. This research was conducted at SMA Negeri 1 Ambawang in the academic year 2020/2021. This research was development research which consists of three phases; analysis, design, and development. The result of the analysis in this research showed that the students lack vocabulary and have little time to get a chance to speak English. The result of this research was an instructional design of storytelling. The result of designing storytelling instruction is formed in a lesson plan of teaching speaking narrative text. The designed storytelling instruction consists of six sections: introduction, observing, guiding, practicing, assessing, and closing. It is recommended that the teacher use storytelling techniques to teach English especially in speaking skill